The Effect of Cyberloafing on Work Procrastination in Employees - Zul Aryanor; Risna Febriani (Universitas Muhammadiyah Banjarmasin, 2023)
Work procrastination is the behavior of delaying the completion of work performed by the individual (procrastinator), by performing other activities that are not related to work. One of the factors causing work procrastination is pleasure-seeking, as internet users who are always comfortable with online situations or cyberloafing. This research is located at PT. GAL and PT. GIJ. This study aims to determine the effect of cyberloafing on work procrastination in employees. This research used quantitative research methods. The sampling in this study used a non-probability sampling technique with a total sampling method of 51 employees. The scales used in this study were the cyberloafing scale and the work procrastination scale, with the Rating Scale scaling model. The results of a simple linear regression test showed that the calculated t value is 2,386 (p < 0,05) while the table t value was 2,009 which means that the calculated t value was greater than the table t, it can be collected that there was a significant influence of cyberloafing on work procrastination in employees. The results of this study indicate that cyberloafing behavior has a significant impact on employee work procrastination. This finding provides deep insights into work procrastination influenced by the tendency to seek pleasure through online activities. Therefore, it is recommended that companies consider policies that reduce employee opportunities for cyberloafing in the workplace. Additionally, enhancing training and awareness about the negative effects of cyberloafing is crucial to enabling employees to manage their internet usage productively and stay focused on their tasks without succumbing to procrastination. These suggestions are expected to improve productivity and employee performance in the workplace.